Metagenomic Approach: Transforming In-Silico Research for Improved Biogas Production - Mukti, Roushney Fatima; Sinthee, Sanjida Sakhawat (International Journal of Applied Sciences and Biotechnology, 2019)
The complexity of the microbial communities and metabolic pathways involved in the microbiological process of biogas production is poorly understood and numerous microorganisms in the fermentation sample of the biogas plant are still unclassified or unknown. The structure and function of microbial communities and the effects of the addition of trace elements are needed to be known, to control and channel the energy sources microbes produce and to capture and store the useful by-products or for targeted screening of novel enzymes. In this review, we discussed an emerging idea that Metagenome sequence data from a biogas-producing microbial community residing in a fermenter of a biogas plant provide the basis for a rational approach to improve the biotechnological process of biogas production. The composition and gene content of a biogas-producing consortium can be determined through metagenomic approach which allows the design of the optimal microbial community structure for any biogas plant for the significant progress in the efficacy and economic improvement of biogas production and biofertilizer of either balanced nutrition or rich in specific element for plant growth produced from the sludge of biogas plant. Biogas-producing microbial community from different production-scale biogas plants supplied with different raw materials as substrates can be analyzed by polyphasic approach to find out the best raw material composition for biogas production. The phylogenetic structure of the microbial community residing in a fermentation sample from a biogas plant can be analysed by an integrated approach using clone library sequences and metagenome sequence data obtained by 454-pyrosequencing. Int. J. Appl. Sci. Biotechnol. Vol 7(1): 6-11